Curcuminoids from Curcuma longaL. reduced intestinal mucositis induced by 5-fluorouracil in mice: Bioadhesive, proliferative, anti-inflammatory and antioxidant effects. (2016) - dos Santos Filho, Edvande Xavier; Ávila, Paulo Henrique Marcelino; Bastos, Carla Caroline Cunha; Batista, Aline Carvalho; Naves, Letícia Nasser; Marreto, Ricardo Neves; Lima, Eliana Martins; Mendonça, Elismauro Frascisco; Valadares, Marize Campos
Abstract: Introduction: Intestinal mucositis is a frequent limiting factor in anticancer therapy and there is currently no broadly effective treatment targeted to cure this side effect. Objective: This study aimed to evaluate the effects of a mucoadhesive formulation containing curcuminoids (MFC) from Curcuma longa L. on the pathogenesis of 5-fluorouracil (5-FU)-induced intestinal mucositis. Methods: Three intraperitoneal 5-FU injections (200 mg/kg) were used to induce intestinal mucositis in adult Swiss male mice. Treatment was provided orally (MFC 3.75, 7.5 and 15 mg/kg), thirty minutes before 5-FU injections, daily until euthanasia. Duodenal samples were collected to perform morphometric and histopathological analysis, to investigate the expression of Ki-67, p53, Bax and Bcl-2 by immunohistochemistry, to evaluate neutrophil activity myeloperoxidase (MPO)-mediated and oxidative stress by malondialdehyde (MDA) determination. Mice body weight was assessed as well. Results: As expected, 5-FU induced a significant weight loss (∼17%, P < 0.001), shortening in villi height (∼55.4%) and crypts depth (∼47%), and increased (∼64%) the histological severity score when compared to other groups ( P < 0.05). These pathological changes were markedly alleviated by the three MFC treatment doses ( P < 0.05), in special with the dose MFC 15 mg/kg. This dose also stimulated cell proliferation by ∼90% in the epithelial cells lining from villi and crypts ( P < 0.05), reduced MPO levels and MDA formation by 60% and 44%, respectively ( P < 0.05). Conclusions: Our data suggest the therapeutic potential of the formulation for treating intestinal mucositis in mice. Supplementary studies are underway searching for the elucidation of mechanisms involved in the protective effects of MFC in order to make this formulation a clinical tool for mucositis treatment.